EFFECT OF Nigella sativa OIL TREATMENT ON THE SEX ORGANS AND SPERM CHARACTORS IN RATS EXPOSED TO HYDROGEN PEROXIDE - Fadwa. Kh. TawfeeK (Mesopotamia Journal of Agriculture)
The effect of Nigella sativa oil (0.8ml/kg B.W) on testis, accessory sex glands and epididymal sperm characters was studied in mature male albino rats treated with hydrogen peroxide H2O2(0.5% in drinking water) for 30 days orally. The results showed thatH2O2 treatment caused a significant decrease in the percentage of live/dead sperms 13.66% associated with a significant increase in the percentage of and morphologically abnormal sperms 39.5%.While a significant increase in the percentage of live/dead sperms in both Nigella sativa oil treated group and Nigella sativa oil joined to H2O2 (85%), (72.16%) , respectively accompanied with a decrease in percentage of morphologically abnormal sperms compared with H2O2 treated group. It is concluded that Nigella sativa oil possess an antioxidative actions to counter act the impairment in the epididymal sperm characters caused by H2O2 treatment.